Strengthening Moral Values Using Prophet Story E-Books for Children Aged 5–6 Years - Rachmawati, Nurin; Tasu’ah, Neneng (Ceria: Jurnal Program Studi Pendidikan Anak Usia Dini, 2025)
Problems concerning moral values among early childhood learners in school settings include dishonest acts such as deceiving friends, lying, taking belongings without permission, damaging peers’ toys and denying responsibility, as well as displaying domineering behavior toward others. Based on these issues, this study aims to examine the effect of strengthening moral values through the use of prophet story e-books among children aged 5–6 years. The study involved a population of 30 children, with the research sample consisting of children aged 5–6 years at TK Pertiwi 2 Dadi, Plaosan District, Magetan Regency, East Java. The research was conducted in May 2025. Data collection techniques included observation, documentation, and questionnaires. A quantitative approach was applied using an experimental method with a pre-experimental design, namely a one-group pretest-posttest research design. The findings revealed that strengthening moral values using prophet story e-books proved highly effective. This is evidenced by a significant increase in the mean score from 120.83 in the pretest to 141.60 in the posttest, indicating an improvement of 20.77 points or approximately 17.2%. It can therefore be concluded that the use of prophet story e-books has a significant impact on strengthening moral values in children aged 5–6 years.